1996
DOI: 10.1148/radiology.199.2.8668777
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of myocardial perfusion imaging with SPECT in the emergency department evaluation of patients with unexplained chest pain.

Abstract: Performing MP imaging in patients with unexplained chest pain while in the emergency department is cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Adapted from Stowers [18]. [17] 50 786 Radensky [19] 209 796 Stowers [18] 180 923 Heller [11] 357 4258 Kontos [21] 874 1014 Ziffer [20] 6548 1900…”
Section: Stress Perfusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted from Stowers [18]. [17] 50 786 Radensky [19] 209 796 Stowers [18] 180 923 Heller [11] 357 4258 Kontos [21] 874 1014 Ziffer [20] 6548 1900…”
Section: Stress Perfusion Imagingmentioning
confidence: 99%
“…There are several studies which evaluated the economic implications of the use of early risk stratification with MPI for assessment of chest pain in the emergency department. Weissman et al[17] used a survey method of decision making by physicians before and after the MPI results were available. They found that 68% of the physicians' decisions were affected by the MPI results and estimated potential cost savings of $786 per patient.…”
mentioning
confidence: 99%
“…[1,2,3••, [4][5][6]. A recently completed multicenter trial randomized 2456 patients presenting to the ED with chest pain and a normal or nondiagnostic ECG to usual care or immediate rest SPECT MPI [7••].…”
Section: Myocardial Perfusion Imagingmentioning
confidence: 99%
“…A larga utilização da cintilografia miocárdica imediata de repouso é limitada pela indisponibilidade do método nas salas de emergência, pela demora na sua realização após um episódio de dor torácica e pelos seus custos. Entretanto, alguns grupos têm preconizado a realização do exame para pacientes com média ou baixa probabilidade de IAM, já que um exame negativo praticamente afasta este diagnóstico 45,93 , permitindo a liberação imediata destes pacientes com conseqüente redução dos custos hospitalares 94,95 . 3.4.3 Ecocardiograma -O papel do ecocardiograma de repouso na avaliação de pacientes na sala de emergência com dor torácica se alicerça em poucos estudos publicados.…”
Section: Cintilografia Miocárdica De Repouso -unclassified